ParentUp! Online positive parenting group counselling intervention that enhances gratitude, self-compassion, and resilience - Raftopoulou, Georgia; Papadimitriou, Anna; Sini, Maria; Daoultzis, Konstantinos Christos; Karakasidou, Eirini (Psychology: the Journal of the Hellenic Psychological Society, 2025)
Parental solid guidance shapes a child’s development, and online support groups can provide accessible resources for parents in today’s digital world. This study tested a 10-week online Positive Psychology Intervention (PPI) program for parents with children aged 7-13. We hypothesised the program would increase parents’ self-compassion, gratitude, and positive emotions. Equal-sized groups (n = 19) were recruited online (experimental and control). The program introduced positive psychology concepts and parenting applications, focusing on emotion regulation, self-compassion, gratitude, and building resilience. Parents completed questionnaires before and after the program, measuring emotions, self-compassion, gratitude, resilience, and demographics. The online format increased flexibility and accessibility. Results showed increased gratitude, self-compassion, resilience, and positive emotions, supporting online PPIs as an effective intervention for parents with children aged 7-13. Children appeared to be also indirectly and positively affected by the change in their parent’s behaviour.